Profile of meat processing industry in Iloilo City - Dairo, Ma. Josefa Buenaflor (1996.)
Twenty out of the twenty six identified local meat processors that produce and sell their products within Iloilo city were personally interviewed in establishing a profile of the meat processing industry in Iloilo City.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Meat processing industry; Industries; Iloilo City